Taphonomical aspects of Testudines from Santana formation (Lower Cretaceous), Araripe Basin, Northeastern Brazil - Oliveira, Gustavo Ribeiro de (Anuário do Instituto de Geociências, 2007)
Araripe Basin is worldwide famous by diverse and exquisitely well preserved fossil assemblages in Santana Formation. This lithostratigraphic unit is subdivided into three members: Crato, Ipubi and Romualdo. Up to date six species of turtles are known: Araripemys barretoi Price, 1973; Santanachelys gaffneyi, Hirayama, 1998; Brasilemys josai Lapparent de Broin, 2000; Cearachelys placidoi Gaffney, Campos & Hirayama, 2001, Euraxemys essweini Gaffney, Tong & Meylan, 2006 and Caririemys violetae Oliveira & Kellner, 2007. Taphonomical features of turtles from Crato and Romualdo members are presents here. One specimen was examined in the Crato lagerstätte, (MN 4893-V) Araripemys sp. (partial skull, axial and apendicular skeleton). This exemplar is preserved in light-beige colored laminated limestone from the Crato Member. Three specimens were analized (MN 6743-V, MN 6744-V and MN 6760-V) in the Romualdo lagerstätte, the two first are Araripemys barretoi specimens (shell and cervical vertebrae) and the later is a Cearachelys placidoi specimen (fragmented shell). They are preserved in calcareous nodules. No data of collection of these specimens are available, however are possible to infer on aspects of preservation of these exemplares, since that these are preserved in the original sedimentary matrix. All specimens have shown the surface of bones without abrasion, what it allows to infer these turtles as autocthonous.